2021
DOI: 10.1038/s41598-021-80961-x
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro study on Staphylococcus schweitzeri virulence

Abstract: Staphylococcus schweitzeri belongs to the Staphylococcus aureus-related complex and is mainly found in African wildlife; no infections in humans are reported yet. Hence, its medical importance is controversial. The aim of this work was to assess the virulence of S. schweitzeri in vitro. The capacity of African S. schweitzeri (n = 58) for invasion, intra- and extracellular cytotoxicity, phagolysosomal escape, coagulase activity, biofilm formation and host cell activation was compared with S. aureus representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Although the previous studies showed that the cultureindependent assays based on detection of MNase activity could provide needed specificity for the detection of S. aureus, homologs of the nuc gene were also found in other species of the S. aureus complex (Grossmann et al 2021). Therefore, we cannot exclude a possibility that infections caused by Staphylococcus schweitzeri (possessing nuc M ) or uncommon coagulase-negative staphylococci may yield false-positive identifications since they were not examined previously (Burghardt et al 2016;López-Álvarez et al 2020).…”
Section: Rapid Detection Of S Aureus Bloodstream Infections Via Nuclease Activitymentioning
confidence: 91%
“…Although the previous studies showed that the cultureindependent assays based on detection of MNase activity could provide needed specificity for the detection of S. aureus, homologs of the nuc gene were also found in other species of the S. aureus complex (Grossmann et al 2021). Therefore, we cannot exclude a possibility that infections caused by Staphylococcus schweitzeri (possessing nuc M ) or uncommon coagulase-negative staphylococci may yield false-positive identifications since they were not examined previously (Burghardt et al 2016;López-Álvarez et al 2020).…”
Section: Rapid Detection Of S Aureus Bloodstream Infections Via Nuclease Activitymentioning
confidence: 91%
“…The isolates were obtained almost exclusively from animals, fruit bats, non-human primates and a gorilla. In three cases, colonization in humans was detected, but these were probably spillover events from handling animals that carried S. schweitzeri [3,10,30]. This low rate was actually surprising, because S. schweitzeri has been found in animals that serve as bushmeat [9].…”
Section: Prevalence Of S Schweitzerimentioning
confidence: 98%
“…Recent studies applied multilocus sequence typing (MLST) or whole genome sequencing to distinguish the members of the S. aureus-related complex [5,6,10,31]. Phylogenetic trees are constructed to identify the closest related species within the S. aureus complex.…”
Section: Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several more clonal complexes have been described to belong to S. argenteus since and multiple studies have elaborated on its worldwide spread, including Australia, Africa, Asia, America and Europe [2]. S. aureus and S. argenteus have been implicated in disease in humans and non-humans [2,3], whereas the closely related S. schweitzeri has been found primarily in bats and non-human primates and no human infections have been described to date [4,5]. Human S. argenteus infections are associated with serious morbidity, mortality and nosocomial infection in humans [3,6], and isolates have been shown to harbor most of the virulence genes of S. aureus [5].…”
Section: Introductionmentioning
confidence: 99%